Preparation, Characterization and Nitrogen Release Behaviour from Urea Ammonium Nitrate Loaded Poly (Acrylic Acid-co-Acrylamide)/Bentonite Based Nanoclay Polymer Composites in Soil - Roy, Dibakar; Kumar, Asheesh; Saini, Ravi; Singh Chauhan, Abhishek Pratap; Manjaiah, K. M. (International Journal of Bio-resource and Stress Management, 2025)
This laboratory study was conducted during October, 2023 to December, 2023 at Indian Agricultural Research Institute, New Delhi and focused on the synthesis, characterization, and evaluation of poly (acrylic acid)-co-acrylamide / bentonite based nanoclay-polymer composites (NCPCs) for their potential application as slow-release nitrogen fertilizers. NCPCs were synthesized by co-polymerization reaction between partially neutralized aqueous acrylic acid solution with acrylamide and bentonite clay (in varied amount; 8, 12 and 16% by weight of acrylic acid), in presence of crosslinker and free radical reaction initiator. The composites were characterized using Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) techniques for physical properties. The water absorption and retention studies revealed high swelling capacities of the NCPCs, enabling gradual water and nitrogen release. Nitrogen release studies revealed that NCPCs loaded with urea ammonium nitrate (UAN) in soil showed a slower (40–60% less total N release over 28 days) and more sustained release compared to conventional UAN fertilizer. NCPCs regulated nitrogen availability by releasing ammonium (NH4+) and NO3 at a slower rate during the incubation period, but the effect was more visible upto 15 days. Further N release from UAN-loaded studied using zero-order, first-order and Higuchi’s kinetic reaction model; results highlighted that N release rate followed first-order kinetic reaction evident from higher R2 (0.93) over others. In conclusion, NCPCs can sustain N availability from UAN in soil for longer duration and offers its suitability for agricultural application for better nutrient use efficiency over conventional UAN fertilizer.